Transnational Organized Crime in West Africa - United Nations Office on Drugs; Crime (United Nations, 2013)
This regional assessment is broadly focused on transnational organized crime (including drug trafficking) issues and the linkages with development, governance and security in West Africa. This Report is intended to provide a more comprehensive and nuanced picture of contraband flows, criminal markets and their political, social and economic impacts on the regions in question. It will be a means to convene strategic dialogue on emerging transnational organized crime threats, and the recommendation it yields will be built back into policy analysis and programme development throughout the United Nations System, including at the regional and country levels.